The Degree of Empowerment of School Leaders in The Integration Programs for Students with Hearing Impairment in The Light of Change Management in The City of Riyadh - Saud G. Albeshir; Faisal F. Sloom (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
The current study aimed to identify the degree to which school leaders in the integration of hearing impairment programs can manage change from the viewpoint of special education teachers. The study sample consisted of 170 teachers of primary hearing impairment integration programs in the city of Riyadh in the modern Kingdom of Saudi Arabia. The researchers developed a questionnaire to measure the degree to which school leaders in programs for integrating the hearing impairment can manage change from the viewpoint of special education teachers. The study found that the degree of empowerment of school leaders in the programs integrating hard-of-hearing students in the planning field was "average." The results of the study also indicated that the degree of empowerment of school leaders in the programs for integrating students with hearing impairment in the field of assessment was "medium," while the degree of empowerment of school leaders in programs for integrating students with hearing impairment in the process of developing a future vision for the school was "high." Furthermore, the study found that the degree of obstacles to implementing change management among school leaders in the integration programs for students with hearing impairment was "high."